2020
DOI: 10.1101/2020.10.29.360719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase separation of the LINE-1 ORF1 protein is mediated by the N-terminus and coiled-coil domain

Abstract: Long Interspersed Nuclear Element-1 (LINE-1 or L1) is a retrotransposable element that autonomously replicates in the human genome, resulting in DNA damage and genomic instability. Activation of L1 in senescent cells triggers a type I interferon response and age-associated inflammation. Two open reading frames encode an ORF1 protein functioning as mRNA chaperone and an ORF2 protein providing catalytic activities necessary for retrotransposition. No function has been identified for the conserved, disordered N-t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…A recent study also described phase separation behavior of ORF1p in biochemical reconstitution experiments (Newton et al 2021). This study characterized the formation of an ORF1p condensed phase that is mediated by electrostatic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also described phase separation behavior of ORF1p in biochemical reconstitution experiments (Newton et al 2021). This study characterized the formation of an ORF1p condensed phase that is mediated by electrostatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ORF1p exhibits all three of these molecular features of phase-separating proteins, we hypothesized that ORF1p undergoes condensation to carry out its roles in L1 RNP formation and chaperoning of L1 machinery. Recent work has confirmed that purified ORF1p is able to form a liquid-like condensed phase in vitro and that a truncated protein containing only the NTR and CC is sufficient for phase separation (Newton et al 2021). Here we demonstrate that ORF1p expressed from a full-length active L1 element rapidly forms cytoplasmic condensates in cells.…”
Section: Introductionmentioning
confidence: 97%
“…RNA and RNA binding proteins (RBPs) are key components of these cytoplasmic condensates 30 . Recently, by microscopy and NMR spectroscopy, human L1 ORF1 protein was shown to form liquid droplets in vitro in a salt dependent manner 31 . To test whether L1 ORF1 foci in mESCs undergo similar LLPS, we treated Dicer_KO mESCs with 3% 1,6 Hexanediol for 15 minutes, a concentration at which proteins undergoing LLPS have been previously observed to change solubility from being in foci to becoming diffused in mESCs 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Constituent subunits of condensates, including SC proteins, can enter and exit condensates and move within them. Coiled-coils can facilitate phase-separation (47, 48), potentially by promoting multivalent interactions (49, 50). This is consistent with the poor per-site conservation of SC proteins, since multivalent interactions can rely on molecular features exhibited by groups of amino acids (e.g., charge or hydrophobicity) rather than tight, ‘lock-and-key’ interfaces formed by specific tertiary structures.…”
Section: Discussionmentioning
confidence: 99%